SUITABILITY OF GROUNDWATER QUALITY FOR DRINKING USING WATER QUALITY INDEX IN KANO METROPOLIS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Groundwater is an important source of drinking water in Kano Metropolis, Nigeria. This study aims to assess the suitability of groundwater for drinking using the water quality index (WQI). 960 water samples were collected from 160 sites in the Kano Metropolis and analyzed 9 physicochemical parameters, 9 heavy metals and two groups of microbial parameters using American Public Health Association standard procedures in a laboratory. The values obtained for the various parameters were then compared to the World Health Organization’s (WHO) and Nigerian Standards for Drinking Water Quality (NSDWQ). The overall WQI for each LGA was calculated using Weighted Arithmetic Index guidelines. The results showed that overall WQI is generally unsuitable for drinking with ranged values of borehole water from 47.07 - 149.51 in Dala and Nasarawa respectively while the well water ranged from 94.17 - 251.44 at Tarauni and Kumbotso and spatially represented in map of Kano metropolis. Marginally suitable for drinking were recorded at Dala and some individual wells in well-planned and clean areas (Bompai Quarters, GRAs). The T-Test statistical analysis between borehole and well in Dala, KMC and Nasarawa LGAs showed significant variations at P = < .05 while Fagge, Gwale, Kumbotso, Tarauni and Ungogo LGAs showed no significant differences. The study recommends the need for improved water management strategies, such as desalination and water treatment, to increase access to safe drinking water.
Keywords: Groundwater; suitability; contaminate; water quality; index; pollution